2017
DOI: 10.1088/1361-6528/aa7d9e
|View full text |Cite
|
Sign up to set email alerts
|

Role of sulphur atoms on stress relaxation and crack propagation in monolayer MoS2

Abstract: We present in-situ transmission electron microscopy of crack propagation in a freestanding monolayer MoS and molecular dynamic analysis of the underlying mechanisms. Chemical vapor deposited monolayer MoS was transferred from sapphire substrate using interfacial etching for defect and contamination minimization. Atomic resolution imaging shows crack tip atoms sustaining 14.5% strain before bond breaking, while the stress field decays at unprecedented rate of 2.15 GPa Å. Crack propagation is seen mostly in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…During the transgranular propagation, stress-concentration is highly localized at Mo atoms of the crack tip (Figure c); however, the stress on S atoms becomes remarkably relieved (Figure S6c). This reveals that the Mo atoms play a crucial role in load bearing, while S atoms are very important in sustaining large stress at the sharp crack tip, in agreement with recent MD calculations . No evident lattice reconstruction in both tip regions is detected.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…During the transgranular propagation, stress-concentration is highly localized at Mo atoms of the crack tip (Figure c); however, the stress on S atoms becomes remarkably relieved (Figure S6c). This reveals that the Mo atoms play a crucial role in load bearing, while S atoms are very important in sustaining large stress at the sharp crack tip, in agreement with recent MD calculations . No evident lattice reconstruction in both tip regions is detected.…”
Section: Resultssupporting
confidence: 89%
“…There have also been a number of pioneering studies examining the mechanical properties of defect-free MoS 2, both experimentally and theoretically. , However, very few attempts have been made to assess the effect of topological defects on the mechanical properties of MoS 2 crystals. Using computer simulations, it was revealed that point defects, including V 1S , V 2S , V Mo , V MoS 2 , and V MoS 3 , degrade the in-plane tensile properties of single-crystal MoS 2 because of stress-concentration at the defect locations. , Very recently, in situ experiments and molecular dynamics (MD) simulations showed that the crack propagating behavior in crystalline domain of CVD-grown monolayer MoS 2 was governed by the concentration of point defects ahead of the crack tip zone and exposed environments. , For example, crack deflections occurred in sparse vacancy defects of MoS 2 crystals, while, as a result of migration of vacancies in the strain fields into networks, a transition from brittle to ductile in fracture mechanism was discovered as the density of vacancy defects exceeds a critical value …”
Section: Resultsmentioning
confidence: 99%
“…This shows that under uniaxial tension loading, the crack tends to propagate along the zigzag edge, implying that the zigzag's edge energy is lower than the armchair's edge energy. In a recently published study, Islam et al 27 explained the crack mechanism that preferentially propagates along the zigzag edge, which is consistent with the previous experimental study 43 for MoS 2 material.
Figure 2 The atomic shear strain evolution and deformation behavior of monolayer MoS 2 membrane under tension ( a ) along the x (armchair) direction at 1 K, ( b ) along the y (zigzag) direction at 1 K.
…”
Section: Resultssupporting
confidence: 76%
“…Our findings can be qualitatively understood in the framework of several theoretical works, , where molecular dynamics simulations show that crack propagation in MoS 2 monolayers is governed by sulfur vacancy concentrations ahead of the crack tip. For pristine MoS 2 , the crack propagates through a preferential direction with the least energy release; sparse vacancies create crack deflection and therefore strain energy.…”
Section: Resultssupporting
confidence: 56%